Dietary essential α-linolenic acid and linoleic acid differentially modulate TNFα-induced NFκB activity in FADS2-deficient HEK-293 cells. (4th July 2017) - Schübel, Ruth; Jaudszus, Anke; Krüger, Ralf; Roth, Alexander; Klempt, Martin; Barth, Stephan Wilhelm
Abstract: The pro- or anti-inflammatory bioactivity of dietary essential linoleic acid (LA) and alpha-linolenic acid (ALA) is mainly attributed to rate-limiting delta-6 desaturase (D6D) activity. The aim of this study was to analyze mechanisms of D6D-substrates ALA, LA and D6D-product gamma-linolenic acid (GLA) under D6D-deficient conditions. Fatty acid profiles (GC-MS), D6D gene expression (real-time RT-PCR) and NFκB activity (luciferase assay) were assessed in HEK293 cells. FADS2 gene expression was approved being marginal. Incubation with ALA or LA did not increase D6D products but their elongase products C20:3 n -3 and C20:2 n -6. Bypassing the D6D, GLA elevated C20:3 n -6 and C20:4 n -6. LA significantly increased (+18% at 60 μM; p  < .001), ALA reduced (−32% at 100 μM; p  < .001) and GLA did not specifically change NFκB activity. Our data indicate that D6D might not be essential for the distinct effects of LA and ALA on NFκB activity.